2010
DOI: 10.1016/j.taap.2009.12.038
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium down-regulation of kidney Sp1 binding to mouse SGLT1 and SGLT2 gene promoters: Possible reaction of cadmium with the zinc finger domain of Sp1

Abstract: Cadmium (Cd) exposure causes glucosuria (glucose in the urine). Previously, it was shown that Cd exposure of primary cultures of mouse kidney cells (PMKC) decreased mRNA levels of the glucose transporters, SGLT1 and SGLT2 and that Sp1 from Cd-exposed cells displayed reduced binding to the GC boxes of the mouse SGLT1 promoter in vitro. Here, we identified a GC box upstream of mouse SGLT2 gene. ChIP assays on PMKC revealed that exposure to 5 μM Cd abolished Sp1 binding to SGLT1 GC box while it decreased Sp1 bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…Nephrotoxicity is one of the main adverse effects of cadmium exposure , and references herein). As a consequence, Cd resulted in inhibition of glucose uptake by kidney and glucosuria (Kothinti et al, 2010), and references herein), which may be in the origin of the hypoglycemia we detected in plasma by metabolomics (Table 2). Growing epidemiological studies have suggested a possible link between Cd exposure and diabetes as Cd induced oxidative stress causes suppression of insulin secretion and apoptosis in pancreatic islet -cell .…”
Section: Carbohydrate Metabolismmentioning
confidence: 79%
“…Nephrotoxicity is one of the main adverse effects of cadmium exposure , and references herein). As a consequence, Cd resulted in inhibition of glucose uptake by kidney and glucosuria (Kothinti et al, 2010), and references herein), which may be in the origin of the hypoglycemia we detected in plasma by metabolomics (Table 2). Growing epidemiological studies have suggested a possible link between Cd exposure and diabetes as Cd induced oxidative stress causes suppression of insulin secretion and apoptosis in pancreatic islet -cell .…”
Section: Carbohydrate Metabolismmentioning
confidence: 79%
“…Thus, human OGG1 (hOGG1), a glycosylase responsible for recognition and excision of the premutagenic 8-oxodG during BER in mammalian cells, was inhibited by cadmium (Potts et al 2003). Even though hOGG1 contains no zinc binding motif itself, its inhibition was shown to be due to diminished DNA binding of the zinc finger containing transcription factor SP1 to the OGG1 promotor (Youn et al 2005), presumably due to displacement of zinc by cadmium (Kothinti et al 2010). Also, a downregulation of DNA repair genes like XPC has been observed recently in cultured cells (Schwerdtle et al 2010) and in vivo (Zhou et al 2004), which may be due to a disturbed transcriptional activity of p53.…”
Section: Molecular Mechanismsmentioning
confidence: 99%
“…Among these low expressed transport-related genes, 10 genes (Slc2a2, Slc5a1, Slc16a2, Slc22a13, Slc22a18, Slc25a11, Slc36a1, Slco6c1, Abca3 and Abcd1) were common between 129/Sv and DBA/2 mice. A previous study showed that Slc5a1 gene expression was downregulated by Cd (Kothinti et al, 2010). To our knowledge, the relationship between Cd and the other remaining genes has not yet been reported.…”
Section: Resultsmentioning
confidence: 78%